Regulation and Evasion of Host Immune Response by African Swine Fever Virus - Wu, Lei; Yang, Bincai; Yuan, Xu; Hong, Jinxuan; Peng, Min; Chen, Ji-Long; Song, Zhongbao (Frontiers in Microbiology, 2021)
Abstract: African Swine Fever (ASF) is an acute lethal hemorrhagic viral disease in domestic pigs and wild boars, and is widely epidemic in Africa, Europe, Asia, and Latin America that pose a huge threat to the pig industry worldwide. ASF is caused by the infection of the African Swine Fever Virus (ASFV), a cytoplasmic double-stranded DNA virus belonging to the Asfarviridae family. Here, we review how the virus regulates host immune response and its mechanisms at different aspects, including interferon, inflammation, apoptosis, antigen-presenting, and cellular immunity.